Phylogenetic analysis of Western Atlantic Bathygobius (Teleostei: Gobiidae) - Tornabene, Luke; Pezold, Frank (Zootaxa, 2011)
The phylogenetic relationships of the Western Atlantic species of Bathygobius are inferred from DNA sequence data from two mitochondrial genes (cytochrome b, cytochrome c oxidase-I) and one nuclear gene (Recombination Activating Gene I). The phylogeny inferred from the concatenated dataset of the three genes uncovered the following major findings: (i) the Western Atlantic species of Bathygobius as a whole are not monophyletic; (ii) a well-supported monophyletic group containing B. soporator, B. lacertus and the Eastern Pacific B. andrei was recovered (termed the B. soporator group); (iii) a well-supported monophyletic group was recovered that contains B. curacao, the Eastern Pacific B. ramosus and B. lineatus, and B. antilliensis (termed the B. antilliensis group); (iv) the relationships between the several lineages of new world Bathygobius and some species of old world Bathygobius could not be resolved, and monophyly of a clade of all new world species could not be determined. The evolutionary history of the Western Atlantic species involves periods of diversification that occurred both before and after the closure of the Isthmus of Panama.